Novel Proton Conducting Membranes from the Combination of Sulfonated Polymers of Polyetheretherketones and Polyphosphazenes Doped with Sulfonated Single‐Walled Carbon Nanotubes. Issue 7 (12th April 2017) - Luo, Tianwei; Xu, Hulin; Li, Zhong; Gao, Shuitao; Ouadah, Amina; Zhang, Zeyu; Zhang, Yanxia; Wang, Fang; Jing, Chaojun; Zhu, Changjin
Abstract : Membranes based on polyetheretherketone and polyphosphazenes are prepared by cross‐linking reaction. Morphological study by the transmission electron microscopy (TEM) indicates that well‐separated nanophase and interconnected ionic channel form in the composite membrane, which can account for the remarkable proton transfer. Abstract : Intent on developing efficient proton exchange membranes used for direct methanol fuel cells as well as hydrogen fuel cells, a series of membranes based on sulfonated polyetheretherketone and sulfonated polyphosphazene‐graft copolymers is prepared by cross‐linking reaction because the former material has good enough mechanical property, while the latter is excellent in the proton transfer. The cross‐linked membranes combine the advantages of the two kinds of polymers. Among them, the membrane poly[(4‐trifluoromethylphenoxy)(4‐methylphenoxy)phosphazene]‐g‐poly {(styrene)11 ‐r‐[4‐(4‐sulfobutyloxy)styrene]33 ‐sulfonated poly(ether ether ketone)75 (CF3 ‐PS11 ‐PSBOS33 ‐SPEEK75) shows a proton conductivity at 0.143 S cm −1 under fully hydrated conditions at 80 °C and performs tensile strength about five times as much as did the sulfonated polyphosphazene membrane CF3 ‐PS11 ‐PSBOS33 . Further doping of sulfonated single‐walled carbon nanotubes (S‐SWCNTs) into the cross‐linked membranes on the screening of additives gives composite membrane CF3 ‐PS11 ‐PSBOS33 ‐SPEEK75‐SWCNT possessing proton conductivity of 0.196 S cm −1, even higher than that of Nafion 117 and a tensile strength comparable to that of Nafion 117. However, this significance of the composite membrane in the proton conduction is not observed in the test with a H2 /air fuel cell when it shows a maximal power density of 280 mW cm −2 at 80 °C, whereas 294 mW cm −2 is observed for CF3 ‐PS11 ‐PSBOS33 ‐SPEEK75.